Warfarin Review: Anticoagulan Compounds and Its Interactions with Other Drugs - Intan Dini Maghfiro; Novia Anggraeni Widiastuti; Yushinta Apriliawati; Deni Ainur Rokhim (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Studi Islam Sunan Doe, 2025)
Blood clots in the body will disrupt human activities. Diseases related to blood activity include blood clots, atrial fibrillation, complications of artificial heart valves, and pulmonary embolism. Treatment that can be done is to take drugs that contain anticoagulants, one of which is warfarin. Method Warfarin is an oral anticoagulant compound that is still often used to prevent blood clots. Warfarin is formed by the synthesis of 4-hydroxycoumarin and benzalacetone. Warfarin inhibits vitamin K synthesis by converting glutamic acid residues to gamma-carboxyglutamic acid residues. However, not all drugs can be taken together with warfarin compounds. There are also some doubtful interactions between warfarin and certain drugs. Warfarin has a narrow therapeutic index so it cannot be given together with several other drugs such as anticonvulsants, NSAIDs , antibiotics, g libenclamide , a miodarone , and statins . It is hoped that with this article, knowledge of warfarin as an anticoagulant will be better in the treatment of diseases caused by blood clots. In this journal, the author uses the literature review method which involves searching and critical analysis of various relevant literary sources, including journal articles, books, and scientific publications related to the topic of discussion.